내관 지압과 심상요법이 방사성요오드 치료를 받는 갑상선암 환자의 오심, 구토, 헛구역질 및 식욕부진에 미치는 효과 - 강미경(Kang, Mi Kyung); 서은영(Suh, Eunyoung, E.) (Asian oncology nursing, 2013)
Purpose: The purpose of this study was to evaluate the effects of P6 acupressure and guided imagery on nausea, vomiting, retching, and anorexia of the patient with thyroid cancer who were undergoing high dose radio-active iodine therapy (HD-RAIT). Methods: Using a randomized control group pretest-posttest study design, the participants were randomly assigned into the control group (C), the experimental group I (E1, P6 acupressure only) and the experimental group II (E2, P6 acupressure and a guided imagery). The patients were recruited from December 2011 to June 2012 in a tertiary hospital in Seoul, South Korea. A total of 82 patients completed the study. The Korean version of the Rhodes INVR and the anorexia scale by Grant (1987) were used. Results: The levels of nausea, vomiting, retching, and anorexia were significantly different among the groups. The levels of nausea and retching especially showed significant group differences over time. Synergic effects of P6 acupressure with guided imagery had significant effects over separate P6 acupressure intervention. Conclusion: Non-pharmacological and nurse-provided P6 acupressure and guided imagery appeared to be effective and safe in reducing nausea, vomiting, retching, and anorexia of the patients with thyroid cancer underwent HD-RAIT.